Hubungan antara Kebiasaan Membaca dan Prokrastinasi Mahasiswa Muslim dengan Keterampilan Menulis Esai Menggunakan Regresi Robust - Siti Musfuji'atun; Choirun Nahdliyin; Umi Mahmudah (IAINU Kebumen, 2023)
This study aims to analyze the effect of Islamic-based students' reading habits and procrastination on their ability to write essays using robust regression. It makes it possible not to test the classical assumptions that must exist in ordinary linear regression analysis. In addition, robust regression is believed to provide better estimation accuracy. A total of 137 Muslim students at UIN K.H. Abdurrahman Wahid Pekalongan was randomly selected for this study. The results of the robust regression analysis using the R program show that the reading habits of Muslim students have a significant effect on the ability to write essays at a significance level of 0.05 (B= 0,691, t-value = 1,801, and p-value = 0,037). In addition, the results of the study also showed that student procrastination had a positive and significant effect on students' writing ability (B= 3,931, t-value = 7,741, and p-value = 0,000). Overall, the results also show that robust regression provides accurate and unbiased estimation results.